Applying the descriptors for “Facilitating the pluricultural space” (Council of Europe, 2020) in an action research study of an L3 English lingua franca telecollaboration - Ellis, Melanie (Neofilolog, 2026)
An action research study, aimed to build intercultural competences and mediation skills through communicative language activities, was conducted by the author during a telecollaboration project between L3 students from universities in Poland (n = 22) and Kyrgyzstan (n = 21). As a pre-post measure of mediation skills, descriptors from the CEFR Companion Volume (CEFRCV) were adapted to create a self-assessment questionnaire. The skills focus was on understanding, being understood and developing positive, empathetic and respectful attitudes across cultures. Participants took part in synchronous computer-mediated communication in-class meetings with tasks to do in small, international groups, involving information exchange and comparing and contrasting. Offline they completed follow up tasks, working in the same groups, communicating as they wished. Data from the self-assessment questionnaires from the Polish students was triangulated with reflections written following the first online encounter, and extracts from interviews made at the end of the project. Statistically significant gains were found on only 2 of the self-assessment statements, and these were corroborated by quantitative and qualitative oral and written data from the participants. Length of the telecollaboration and alignment between tasks and the questionnaire are suggested as possible factors for the moderate changes in mediation skills noted. Reflections are made on possible changes to procedure, tasks and the self-assessment instrument.